2019
DOI: 10.31234/osf.io/pgsqy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Syllables are Retrieved before Segments in Mandarin Chinese Spoken Production: An ERP study

Abstract: Languages may differ regarding the functional units of word-from encoding in spoken word production. It is widely accepted that segments are the primary units in Indo-European languages. However, it is controversial what are the functional units (syllables or segments) in Chinese spoken word production. In the present study, Mandarin Chinese speakers named pictures while ignoring distractor words presented simultaneously, which were share atonal syllables, initial segments or final segments with the name of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…As pointed out by Bürki (2017), the stimulus-locked ERP analysis could probe into the early phonological encoding processes shortly after the presence of the stimulus, but only the response-locked ERP analysis could tap into the late motor preparation processes close to articulation. However, nearly all the current EEG studies on Chinese word production only focused on the ERPs time-locked to the stimulus onset (e.g., Cai et al, 2020;Feng et al, 2019;Qu et al, 2020), which may fail to capture the later motor planning processes (Laganaro, 2014). Thus, a combination of stimulus-locked and response-locked ERP allowed us to investigate the entire production process, which could offer new insights into the time course issue.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out by Bürki (2017), the stimulus-locked ERP analysis could probe into the early phonological encoding processes shortly after the presence of the stimulus, but only the response-locked ERP analysis could tap into the late motor preparation processes close to articulation. However, nearly all the current EEG studies on Chinese word production only focused on the ERPs time-locked to the stimulus onset (e.g., Cai et al, 2020;Feng et al, 2019;Qu et al, 2020), which may fail to capture the later motor planning processes (Laganaro, 2014). Thus, a combination of stimulus-locked and response-locked ERP allowed us to investigate the entire production process, which could offer new insights into the time course issue.…”
Section: The Present Studymentioning
confidence: 99%
“…There were three types of primes (see Appendix 1 in supplementary materials): a T3 prime (underlying form, e.g., 语, yǔ, 'language/speech'), a T2 prime (surface form, e.g., 鱼, yú, 'fish'), and a control prime (tonally-unrelated, carrying T1 or T4, e.g., 玉, yù, 'jade'). Due to the limited number of available items, following several prior studies on speech production (e.g., Cai, et al, 2020;Feng et al, 2019;Q. Zhang and Damian, 2019), the target pictures were presented with all three types of primes for each participant.…”
Section: Design and Stimulimentioning
confidence: 99%
“…They argued that similar to L1 English speakers, native-Mandarin speakers undergo a restructuring of their phonological mental lexicons from a system that is biased towards a syllable grain size to a system sensitive to segmental units. Variation in L2 English proficiency might also explain why in neurological examinations of speech encoding researchers have found evidence of segmental processing (Qu, Damian, and Kazanina 2012;Yu, Mo, and Mo 2014), syllabic processing (Feng, Yue, & Zhang, 2019;Zhang & Damian, 2019); and both segmental and syllabic processing (Cai, Yin, & Zhang, 2020;Yu, Mo, Li, & Mo, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such a rhyme effect has been observed in English as well and localized at an early stage before motor output (Lupker, 1982). Moreover, in another Chinese word production study, Feng et al (2019) combined the PWI paradigm with the technique of event-related brain potential and found that the rhyme effect occurred more than 60 milliseconds (ms) later than the syllable effect did, suggesting that syllabic and sub-syllabic effects originate from different processes during production (i.e., the syllable-to-tone association process and the subsequent segmental specification process). This result is consistent with the findings of previous PWI studies which compared the time course of processing syllables and syllable bodies in Chinese word production (Wang et al, 2018; Wong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%